2022
DOI: 10.3390/pathogens11101172
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Trypanosoma cruzi Congenital Transmission

Abstract: Chagas disease, initiated by the etiological agent Trypanosoma cruzi, is an endemic infection in the American continent. Although vectorial transmission of T. cruzi is recognized as the main mode of infection, other routes such as congenital and blood transfusion are also documented as important methods of transmission. T. cruzi maternal–fetal transmission has been recorded in humans and examined by some investigators in naturally and experimentally infected mammals. Dogs are recognized as the major reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…However, in both cases, the hemochorial placenta enables direct contact between fetal trophoblast cells and maternal blood 34 . The notable difference in placental villous structure between mice and humans is related to maternal-fetal exchange and endocrine functions 36 . Among the various similarities and differences in anatomy and histology between human and mouse placentas, mice offer a valuable model for comprehending the impact of various stimuli on pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in both cases, the hemochorial placenta enables direct contact between fetal trophoblast cells and maternal blood 34 . The notable difference in placental villous structure between mice and humans is related to maternal-fetal exchange and endocrine functions 36 . Among the various similarities and differences in anatomy and histology between human and mouse placentas, mice offer a valuable model for comprehending the impact of various stimuli on pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have found parasitic lesions in placental tissues at the marginal zone ( Fernandez-Aguilar et al, 2005 ). These observations suggest that T. cruzi may reach umbilical and fetal capillaries either by infecting SYNs or through invasion of the marginal sinus epithelial cells ( Carlier et al, 2020 ; Avalos-Borges et al, 2022 ).…”
Section: Introductionmentioning
confidence: 95%
“…The main mechanisms and immunoregulatory factors that modulate T. cruzi fetal infection have yet to be determined. Several animal and ex vivo models have been used to study CD congenital transmission ( Avalos-Borges et al, 2022 ). For instance, modulation of the NF-κB and Toll-like receptors (TLRs) pathways, as well as the role of the placental barrier integrity in parasite infection have been evaluated in chorionic villi explants ( Diaz-Lujan et al, 2016 ; Liempi et al, 2016 ; Castillo et al, 2017a , b ) and cord blood cells ( Ait Djebbara et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…15 It has been shown that the activity of nitric oxide is a key factor for limiting placental infection, 16,17 and it is well established that the expression of nitric oxide is stimulated by pro-inflammatory cytokines. 7,18 However, little is known about the source of the cytokines found in the sera of the pregnant women with Chagas, or about the immunological response of the specific placental cells. In addition, there is little knowledge available concerning the expression of cytokines and their role during the first contact between placental barrier structures and T. cruzi during the phase of invasion and multiplication of the parasite within the placental chorionic villous.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the activity of nitric oxide is a key factor for limiting placental infection, 16,17 and it is well established that the expression of nitric oxide is stimulated by pro‐inflammatory cytokines 7,18 . However, little is known about the source of the cytokines found in the sera of the pregnant women with Chagas, or about the immunological response of the specific placental cells.…”
Section: Introductionmentioning
confidence: 99%